Histories of Sensibilities : Visions of Gender, Race, and Emotions in the Global Enlightenment - Isabel Burdiel; Ester García Moscardó; Elena Serrano (Routledge, 2025)
Histories of Sensibilities: Visions of Gender, Race, and Emotions in the Global Enlightenment explores the historical and plural character of sensibility in the Global Enlightenment.From Tahiti to New Orleans to the Mariana Islands; to Lima, Geneva, London, Oviedo, or Venice, the book investigates how sensibility was brandished by different ethnic, political, and cultural groups to define their identities; how cross-cultural and cross-chronological encounters reconfigured ideas of gendered selves; how sexuality was used to empower or subjugate non-European ethnicities; and how the circulation of theories about the origin of emotions and taste reinforced or challenged hegemonic ideas of masculinity and femininity.With a primary focus on Southern Europe and the Hispanic World, areas still not well-charted, this edited collection explores the varied forms in which notions of sensibilities circulated within Europe and between Europe, the Americas, and the Hispanic-Asian Pacific, questioning normative and diffusionist views.Histories of Sensibilities is aimed at postgraduate students and scholars researching the histories of literature and science, cultural studies, the history of emotions, gender studies, and women's history; as well as scholars of Hispanic studies, Latin-America studies, and European studies.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-No Derivatives (CC-BY-ND) 4.0 license.